PENGARUH KINERJA LINGKUNGAN DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA - Wigiarni, Kesdha Rizki; Chandra, Santoso (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study was to determine the effect of environmental performance, profitability, firm size, board of director on firm value. In addition, this study uses audit committee, institutional ownership and capital structure to determine the effect on firm value. The population of this study are manufacturing companies listed on Indonesia Stock Exchange during 2019 – 2021 period. The sampling technique use purposive sampling with the results of 35 companies which were tested using multiple linear regression. The following results from this study indicate that environmental performance, profitability, audit committee, institutional ownership and capital structure has no effect on firm value. While, company size and board of directors affect firm value because each of these variables can attract investors to invest.